Eliteuniversitäten - Gewinner im Wettbewerb um Studierende? - Kerstin Bruckmeier; Georg-Benedikt Fischer; Berthold U. Wigger (Wirtschaftsdienst, 2014)
Zur gezielten Förderung von Wissenschaft und Forschung an den Universitäten hat die Politik 2005 die Exzellenzinitiative ins Leben gerufen. Die Gewinner des Wettbewerbs um Fördergelder wurden fortan als 'Eliteuniversitäten' bezeichnet. Der folgende Beitrag untersucht, ob die Zahl der Studierenden im Erstsemester an den Universitäten mit Elitestatus gestiegen ist. – – The German Excellence Initiative was intended to strengthen university-based research and to create a set of internationally competitive elite institutions. The present article analyses whether or not designation as an elite institution has had an impact on the number of first-year students. Our results indicate that this is not the case. This observation might be explained by the fact that the Excellence Initiative mainly focuses on the reputation of the university as a whole, while students are more interested in the reputation of their preferred field of study. Hence, students compare the quality of faculties or degree programmes rather than the reputation of universities.
Keywords: I21; I22; I28; 330; Hochschule; Elite; Hochschulreform; Studierende; Deutschland